2012
DOI: 10.1111/j.1471-1842.2012.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical literature searches: a comparison of PubMed and Google Scholar

Abstract: Background: Medical literature searches provide critical information for clinicians. However, the best strategy for identifying relevant high-quality literature is unknown. Objectives: We compared search results using PubMed and Google Scholar on four clinical questions and analysed these results with respect to article relevance and quality. Methods: Abstracts from the first 20 citations for each search were classified into three relevance categories. We used the weighted kappa statistic to analyse reviewer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 21 publications
(27 reference statements)
1
63
0
5
Order By: Relevance
“…A consensus seemed to emerge that GS was not as current as PubMed and some expert searchers placed it a year behind or more [7]. Searchers also noticed that PubMed and Google Scholar fulfilled different purposes [10]. In head-to-head comparisons with curated databases, GS was deemed inadequate for subject searching and did not offer what expert searchers wanted to see in a literature database.…”
Section: Introductionmentioning
confidence: 99%
“…A consensus seemed to emerge that GS was not as current as PubMed and some expert searchers placed it a year behind or more [7]. Searchers also noticed that PubMed and Google Scholar fulfilled different purposes [10]. In head-to-head comparisons with curated databases, GS was deemed inadequate for subject searching and did not offer what expert searchers wanted to see in a literature database.…”
Section: Introductionmentioning
confidence: 99%
“…Web of Science is a standard search engine for identifying peer-reviewed studies. Google Scholar was preferred over PubMed because a previous study comparing both search engines revealed that articles found using Google Scholar were more relevant, had more citations, and were published in journals with higher impact scores (Nourbakhsh, Nugent, Wang, Cevik, & Nugent, 2012). Inclusion criteria required that the study be published in a peer review outlet, focused on a U.S. sample, and examined the extent to which a change in the law or practice was causally related to change in maltreatment prevalence or incidence.…”
Section: Review Methodologymentioning
confidence: 99%
“…Dedicated online resources with clinical calculators and providers of aggregated medical information were used (UpToDate, Merck/Univadis, and Medscape) [12][13][14]. Names of available clinical calculators were extracted.…”
Section: Data Sourcesmentioning
confidence: 99%